The Effect of Incentives on Real Effort: Evidence from the Slider Task - Felipe Augusto de Araujo; Erin Carbone; Lynn Conell-Price; Marli W. Dunietz; Ania Jaroszewicz; Rachel Landsman; Diego Lamé; Lise Vesterlund; Stephanie Wang; Alistair J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2015)
Real-effort experiments are frequently used when examining a response to incentives. For any particular real-effort task to be well-suited for such an exercise, subjects' cost for exerting effort must, for the range of incentives considered, result in an interior effort choice. The popular slider task in Gill and Prowse (2012) has been characterized as satisfying this requirement, and the task has been increasingly used to investigate the response to changes in both monetary and nonmonetary incentives. However, despite its increasing use, a simple between-subject examination of the slider task's response to incentives has not been conducted. We provide such an examination with three different piece-rate incentives: half a cent, two cents, and eight cents per slider completed. We find that participants in the three treatments completed on average 26.1, 26.6 and 27.3 sliders per round, respectively. The one-slider increase in observed performance is small, not only relative to the sixteen-fold increase in the incentives, but also relative to the observed heterogeneity across subjects, rates of learning, and even idiosyncratic variation. Our paper cautions that the slider task will be underpowered for uncovering a response to incentives in between-subject designs.
Keywords: C90; C91; 330; slider task; real effort; experimental methodology